The influence of heat treatment condition on electrical properties of glass-ceramics containing ferroelectric lead bismuth germanate ((Pb 3Bi 2(GeO 4) 3) - Nuttapon Pisitpipathisin (2018)
Glasses have been formed from PbO-Bi3O2-GeO2system by conventional meltquenching method. The glasses were melted in Pt crucible in an air atmosphere. The resulting glass pieces were subjected to the heat treatment schedule at various crystallization temperatures. The glass and glass-ceramics samples were then investigated by XRD and SEM spectroscopy. The dielectric and ferroelectric properties were also measured. Moreover, DTA analysis has been used to examine the crystallization temperatures of glasses. The controlled heat treatment process has been applied to the crystallization temperatures and glass-ceramic samples were obtained. The XRD showed that the crystals of ferroelectric phase, hexagonal Pb3Bi2(GeO4)3;PBG, were precipitated in the glass matrix and this is the dominant phase in the region of 34.50 mol% PbO: 11.49 mol% Bi2O3: 54.01 mol% GeO2on the heat treatment temperature at 527°C. The dielectric constant (er) and P-E loop of Pb3Bi2(GeO4)3glass-ceramic confirmed that this material may have high possibility to be ferroelectric at room temperature with coercive field (Ec) of 30.9 kV/cm. However, the remanent polarization (Pr) = 1.36 μC/cm2is rather small, therefore it is quite difficult to confirm that the P-E loop is the feature of truly ferroelectric, it may represent a lossy capacitor behavior. Copyright © Taylor & Francis Group, LLC.